The local determinants of crime victimization - Camille Hemet (European Regional Science Association (ERSA), 2015)
This paper explores the determinants of crime victimization at the neighborhood level, using data from the French victimization survey. The very local nature of the data enables me to tackle the endogenous location selection issue: once I control for the characteristics of a larger area into which household select their location, the remaining variation of observables across neighborhoods within this larger area can be considered as exogenous. The contribution of this paper to the economics of crime literature is then twofold. First, I show that neighborhood characteristics are important determinants of crime victimization. In particular, local unemployment rate is found to be one of the most important factor explaining victimization. Second, I take advantage of the precise localization of the data to adopt a spatial approach, comparing the effect of unemployment rate in the reference neighborhood and in adjacent neighborhoods. The results support the idea that criminals are mobile across neighborhoods for more serious economic crimes, in line with the Beckerian theory of crime, but that petty crimes and vandalism do not involve any mobility, relating to the social disorganization theory.
Keywords: K42; R23; J64; 330; crime; neighborhood effects; unemployment; urban and spatial economics